LEGAL FOUNDATIONS OF VOCATIONAL AND CAREER DEVELOPMENT OF CIVIL SERVANTS - A. Suvorov (Publishing House of the State University of Management, 2016)
The article presents the analysis of the legal foundations of vocational and career development of civil servants. The basic directions of improvement of the current legislation, the system of personnel selection and career growth of civil servants. On the basis of generalization of the results of the analysis highlighted a number of circumstances hindering the implementation of vocational and career development of civil servants in Russia.